Being Fed Through Nostrils Is Described by Alice Paul (1909): Young American Suffragette Inventor of Hunger Strike Tells how British Prison Physicians Keep Life in Women who won’t Eat or Wear Clothes (Clinical Sociology Review, 2023)
London, Dec. 9- Miss Alice Paul, of Philadelphia, the suffragette who was arrested Nov. 9th and sentenced to a month’s hard labor for her share in the suffragette demonstration at the Lord Mayor’s banquet at the Guildhall, was released from Holloway Jail this morning on the completion of her thirty days. She left the prison in a cab, accompanied by two wardresses, and went to the home of friends. A doctor was immediately called to attend her there, owing to her weakened condition.